Association of D-dimer Levels with Clinical Event Rates and the Efficacy of Betrixaban versus Enoxaparin in the APEX Trial - Gibson, C. Michael; Jennings, Lisa K.; Chi, Gerald; Yee, Megan K.; Halaby, Rim; Nafee, Tarek; AlKhalfan, Fahad; Kerneis, Mathieu; Korjian, Serge; Daaboul, Yazan; Goldhaber, Samuel Z.; Hull, Russel D.; Hernandez, Adrian F.; Cohen, Alexander T.; Harrington, Robert A. (TH Open, 2018)
Background Elevated D-dimer concentrations are associated with an increased risk of venous thromboembolism (VTE). However, they may also provide prognostic value. The present analysis sought to study the association of D-dimer levels with VTE event rates and the efficacy of betrixaban versus enoxaparin in the APEX trial.Methods Hospitalized acutely medically ill subjects (n = 7,513) were randomized in a double-dummy double-blind fashion to either extended-duration oral betrixaban (80 mg once daily for 35–42 days) or standard dose subcutaneous enoxaparin (40 mg once daily for 10 ± 4 days) for venous thromboprophylaxis. D-dimer was assessed using a central core laboratory measurement.Results For every 0.25 µg/mL increase in D-dimer concentration, there was a 2% increase in the relative risk of experiencing the primary efficacy endpoint (asymptomatic deep vein thrombosis [DVT], symptomatic DVT, nonfatal pulmonary embolism, or VTE-related death) in both the betrixaban (p < 0.001) and enoxaparin (p < 0.001) treatment arms. Among D-dimer-positive (≥ 2 × upper limit of normal; corresponding to ≥ 1.00 µg/mL) subjects, extended-duration betrixaban reduced the risk of experiencing the primary efficacy outcome (5.4% [n = 124] vs. 7.6% [n = 170]; odds ratio = 0.69; 95% confidence interval: 0.55–0.88; absolute risk reduction = 2.2%, number needed to treat = 46, p = 0.003). There was no interaction between D-dimer and the treatment effect (pint = 0.53).Conclusion Extended-duration betrixaban was superior to standard-duration enoxaparin, irrespective of D-dimer level at baseline. To prevent one VTE event, 46 D-dimer-positive patients would need to be treated with betrixaban.
Keywords: D-dimer; betrixaban; deep vein thrombosis; pulmonary embolism; venous thromboembolism